Flagellin FLiS improves the resistance of cotton to Verticillium wilt through the signaling pathways of salicylic acid and jasmonic acid - Liu, Yujing (Frontiers in Plant Science, 2025)
Verticillium wilt of cotton is a soil-borne vascular bundle disease. There is still a lack of effective methods for controlling and preventing Verticillium wilt of cotton. There are few reports on the research of the mechanism by which flagellin S (FLiS) protein induces cotton immunity. The mechanism by which the FLiS protein induces immune responses in cotton was analyzed through prokaryotic expression and purification, physiological and biochemical techniques, and qRT-PCR (quantitative real-time polymerase chain reaction) technology. The purpose of this study was to determine the role and mechanism of FLiS in improving the resistance of cotton to Verticillium wilt. An endophytic bacterium (Pseudomonas) was isolated from the roots of upland cotton cultivar Zhongmian 44, and the FLiS gene was cloned. The FLiS protein purified in vitro can induce a hypersensitive response (HR) in tobacco, indicating that it is an active protein. In addition, it is capable of triggering an immune response in upland cotton, thereby enhancing the resistance to Verticillium wilt. The FLiS protein can induce the production of hydrogen peroxide(H2O2), callose, and defense enzymes in cotton, as well as the expression of disease resistance genes in the signaling pathways of salicylic acid (SA) and jasmonic acid (JA). FLiS can be used as a biological regulator to improve the resistance of upland cotton to V. dahliae.